TASKS, STAGES, AND BASIC METHODOLOGY OF TECHNICAL TRAINING OF AN ATHLETE - Samekeev Izzet Muratovich (European Science Publishing, 2024)
This comprehensive guide elaborates on advanced strategies and insights to enhance the technical training of athletes. It outlines various cutting-edge approaches, such as deliberate practice, game-specific scenarios, biomechanical analysis, expert coaching, and mind-body connection, to optimize skill development and performance outcomes. The article emphasizes the importance of holistic training, periodic skill assessments, simulation methods, and deliberate practice in fostering athlete growth and success.
Keywords: Technical training, athletes, advanced strategies, deliberate practice, biomechanical analysis, expert coaching, mind body connection.